Analisa Karakteristik Dan Distribusi Hujan Pada Kawasan DAS Batang Hari Kabupaten Dharmasraya - Hartati - - (Jurnal Ilmiah Poli Rekayasa, 2019)
Batang Hari is the 2nd biggest DAS in Indonesia. About 76% of Batang Hari DAS is located in Jambi Province, the entire 24%is in West Sumatera Province. Batang Hari dam which was built on 1997 is one of infrastrcture at Public Work ministery under management at Balai Wilayah Sungai Sumatera V (BWSS V) his high potential of water stock. Optimum discharge of Batang Hari Dam is about 86 m3/sec. In the recently years DAS Batang Hari has been disturbed by some changes like catchment area utilized fot other purpose, change on global climate done to greenhouse effectwhich causingintensity of rain as well as flood. This climate change then will affected standard for engineering design for making a water control buiding which may injuireaccurate waterfall intensity data. Study of rainfall intensity obtained from 3 (three) nearby stations will show the characteristic dam trend of distribution with reperted period. Cousistency of data using Mass Curve method and local rain analysis to be done by Arithmatic & Thiessen Polygon method. To analysis trend of rainfall distribution. We use : Normal, Log Normal, Log Person type III and Gumbel methods. For complaince test of distribution, we use Chi-Kuadrat and Smirnov-Kolmogorov methods. Refer to result of distribution using Chi-Kuadrat and Smirnov-Kolmogorov methods for Arithmatic methods it is adviced to use Gumbel method to evaluate distribution trend; because critical deviation is smell comparing to available in table, with rainfall with repeating period 2,5,10,25,50 and 100 years are 124,08 mm, 1168,56 mm, 198,01 mm, 235,22 mm, 262,83 mm, 290,23 mm and Thiessen Polygon 106,93 mm, 138,22 mm, 158,94 mm, 185,11 mm, 204,53 mm, 223,81 mm